Saatnya Millenial Berwirausaha Mandiri, Kreatif dan Inovatif - Marsadi Aras (Jurnal Pengabdian Teratai, 2020)
This implementation of community devotion aims to : (1) Present the definition of entrepreneurship, (2) Promote motivation for being young entrepreneur, (3) Give insight about the advantage of being entrepreneur, and (4) Provide the opportunity for employment. By implementing this community devotion, hopefully, the UMKM will get to knowIBI Kosgoro 57 better and that they can recocnize the capability of getting knowledge theoretically, as well as consulting comprehensively that can be received in this university. Even as simple as sharing insightand experiences about entreprenership could be obtained as provision and mativation in developing business as well as being comparison to what they have accomplished. This community devotion also provides a good opportunity for IBI Kongoro 57 lecturers in trem of public services. As for the student and alumni, they are expected to have more open mind and a strong desire mind to try and dive into the entrepreneurhip world after this seminar.